A retrospective study of maternal mortality in a tertiary care hospital in Western Maharashtra, India - Gaikwad, Nandkishore B.; M., Poornima; Lad, Reshma M. (International Journal of Research in Medical Sciences, 2020)
Background: Maternal mortality is a vital index of the effectiveness of obstetric services prevailing in a country. The key to progress of a country lies in reducing its maternal morbidity and mortality, hence to give a better assessment of the problem a retrospective study on maternal mortality was carried out. An objective of the study was to find the cause and epidemiological factors for maternal mortality in a tertiary care hospital in western Maharashtra from January 2018 to August 2019. Methods: A retrospective, descriptive study done at tertiary care hospital in western Maharashtra from January 2018 to august 2019. Data was collected from medical records department and the study was conducted by reviewing the records of maternal death and scrutinizing for various aspects likely to be related to maternal death such as age, locality of residence, antenatal care, admission death time interval and cause of death. Results: during the study period 63 maternal deaths occurred and 75302 live births, Maternal Mortality Ratio were 83.66 per 1 lakh live birth. 46% of maternal deaths were in age group of 21-25 years, 87% of patients belonged to rural area, 74% belonged to lower socioeconomic status. 43% were unregistered patients, 43% had vaginal delivery, 73% had no free transportation, 68% were referred patients, 60% were referred from private hospitals, 48% of maternal death occurred <24 hours, 73% of maternal death were due to direct cause, 28% of maternal deaths were due to pre-eclampsia and its complications, 15.8% due to sepsis and 12.6% due to Postpartum hemorrhage. Conclusions: Being a tertiary care hospital, where patients are referred from periphery maternal mortality was found to be on higher side. Proper implementation of government policies with community participation along with strengthening of First Referral Unit (FRU) and Primary Health Centres can help to reduce maternal mortality.